Indonesian Students’ Mathematical Representation Ability According To Learning Styles: Systematic Literature Review - Inayah, Clara Fadhilah; Dahlan, Jarnawi A.; Darhim, Darhim; Maghfiroh, Fitria (Universitas Wiralodra, 2024)
The purpose of this research is to explain the outcomes of Indonesian students' mathematical representation ability according to learning styles. The learning styles are visual, auditory, and kinesthetic. A systematic literature review (SLR) is the research methodology employed in this study. This study used data from 18 papers about mathematical representation ability according to learning styles. Publications published in Indonesia between 2015 and 2023 that are indexed by Google Scholar, SINTA, or Scopus form the publishing data. According to the publication year, the media in which it was published, the research methods employed, the subject's educational background, the research location, and the research findings, the description of this study was reviewed. The most research on mathematical representation ability according to learning styles was found to have been published in 2023, according to SLR. The most prominent research media that published the most research were SINTA and Google Scholar. Qualitative methods dominated this study, with junior high school students serving as the majority of research subjects and the island of Java serving as the most prominent research location in Indonesia. Furthermore, it could be stated that one of the elements influencing mathematical representation ability is learning styles.